2014
DOI: 10.5152/tjar.2014.87487
|View full text |Cite
|
Sign up to set email alerts
|

The Professional Experience of Anaesthesiologists in Proper Inflation of Laryngeal Mask and Endotracheal Tube Cuff

Abstract: Objective: Cuffs inflated to inappropriately high pressures cause ischemia, reducing tracheal mucosal blood flow, while cuffs inflated at lower pressure than necessary give rise to inadequate ventilation, aspiration of gastric contents, or extubation due to air leakage. In this study, we aimed to investigate the effect of the experience of anaesthesia staff on endotracheal tube and laryngeal mask airway cuff inflation. Methods:The study included 348 elective patients scheduled to undergo surgery under general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
1
11
0
1
Order By: Relevance
“…It has been shown to overinflate the cuff in 30-98% of cases, depending on the type of ETT used and the population studied (15). Saraçoğlu et al (16) found no significant relationship between anesthesiologist experience and adequacy of ETT cuff pressure when patients were instructed to inflate the cuff to the level they considered appropriate(17)(17)(17) manually. Bulamba et al (18) suggest using a loss-ofresistance syringe as an alternative to simple palpation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to overinflate the cuff in 30-98% of cases, depending on the type of ETT used and the population studied (15). Saraçoğlu et al (16) found no significant relationship between anesthesiologist experience and adequacy of ETT cuff pressure when patients were instructed to inflate the cuff to the level they considered appropriate(17)(17)(17) manually. Bulamba et al (18) suggest using a loss-ofresistance syringe as an alternative to simple palpation.…”
Section: Discussionmentioning
confidence: 99%
“…Wujtewicz og Sawicka ( 30) viste derimot at cufftrykkene økte ved økt erfaring. Andre studier viser ingen signifikant forskjell mellom erfaring og cufftrykk (8,31,32). Selv om det var et økt antall akseptable cufftrykkverdier ved økt erfaring i Ozer og Demirel (11) sin studie, var over halvparten (56 %) av cufftrykkene til de mest erfarne utenfor de akseptable grensene.…”
Section: Diskusjonunclassified
“…The rapid, qualitative evaluation of the pilot balloon via manual palpation can serve as a surrogate estimation of intracuff pressure, but this method is subject to inherent inaccuracies and does not provide any quantitative data. Saraçoğlu et al [62] demonstrated that there was no significant correlation between the experience of the anaesthesia provider and the appropriateness of the ETT intracuff pressure when subjects were instructed to manually inflate the cuff to what they deemed as an appropriate amount. Harm et al [63] showed that not only do anaesthesia providers frequently misjudge pressures but persons responsible for prehospital intubations do as well.…”
Section: Manual Palpation Of Pilot Balloonmentioning
confidence: 99%